Calcium plus vitamin D supplementation affects glucose metabolism and lipid concentrations in overweight and obese vitamin D deficient women with polycystic ovary syndrome. Issue 4 (August 2015) - Asemi, Zatollah; Foroozanfard, Fatemeh; Hashemi, Teibeh; Bahmani, Fereshteh; Jamilian, Mehri; Esmaillzadeh, Ahmad
Summary Background & aims Few studies have examined the effects of calcium plus vitamin D supplementation on glucose metabolism and lipid concentrations in overweight and obese vitamin D deficient women with polycystic ovary syndrome (PCOS). This study was conducted to determine the effects of calcium plus vitamin D supplementation on glucose metabolism and lipid concentrations among overweight and obese vitamin D deficient women with PCOS. Methods This randomized double-blind placebo-controlled clinical trial was conducted among 104 overweight and obese vitamin D deficient women diagnosed with PCOS. Participants were randomly assigned into four groups to receive: 1) 1000 mg/d calcium + vitamin D placebo (n = 26); 2) 50, 000 IU/wk vitamin D + calcium placebo (n = 26); 3) 1000 mg calcium/d + 50, 000 IU/wk vitamin D (n = 26) and 4) calcium placebo + vitamin D placebo (n = 26) for 8 weeks. Fasting blood samples were taken at baseline and after 8 weeks' intervention to measure glucose metabolism and lipid concentrations. Results Calcium-vitamin D co-supplementation resulted in higher levels of serum calcium (P = 0.002) and vitamin D (P < 0.001) compared with other groups. Co-supplementation, compared with other groups, led to decreased serum insulin levels (P = 0.03), homeostasis model of assessment-insulin resistance (HOMA-IR) score (P = 0.04) and a significant rise in quantitative insulin sensitivity check index (QUICKI) (P = 0.001). Furthermore, a significant decrease in serum triglycerides (P = 0.02) and VLDL-cholesterol levels (P = 0.02) was seen following the administration of calcium plus vitamin D supplements compared with the other groups. Co-supplementation with calcium and vitamin D had no significant effects on FPG, total-, LDL-, HDL-, and non-HDL-cholesterol levels. Conclusions In conclusion, calcium plus vitamin D supplementation for eight weeks among vitamin D deficient women with PCOS had beneficial effects on serum insulin levels, HOMA-IR, QUICKI, serum triglycerides and VLDL-cholesterol levels, but it did not affect FPG and other lipid profiles. Clinical registration numberwww.irct.ir: IRCT201309275623N10